2016
DOI: 10.14202/vetworld.2016.1478-1484
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary supplementation of salts of organic acid on production performance of laying hens

Abstract: Aim:An experiment was conducted to evaluate the effect of supplementing different levels of salts of organic acid in the laying hen’s diet on their production performance and egg quality parameters during a period of 16-week.Materials and Methods:A total of 140 white leghorn laying hens at 24 weeks of age were randomly distributed to seven dietary treatment groups, i.e. T1 (control), T2 (0.5% sodium-butyrate), T3 (1.0% sodium-butyrate), T4 (1.5% sodium-butyrate), T5 (0.5% calcium-propionate), T6 (1.0% calcium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
12
0
2
Order By: Relevance
“…Hassan and Raheem (2016) also observed that feeding benzoic acid to broilers had no significant effect on body weight, weight gain, feed intake, and feed conversion ratio. While it has been reported that organic acid did not influence feed intake in laying hens ( Dahiya et al., 2016 ), it has been shown that organic acid can increase egg weigh ( Grashorn et al., 2013 ). The results of this study highlight the inconsistency of the responses to acidifiers which could be because of several factors including the buffering nature of some dietary ingredients and the heterogeneity of the gastrointestinal microbiota ( Pearlin et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hassan and Raheem (2016) also observed that feeding benzoic acid to broilers had no significant effect on body weight, weight gain, feed intake, and feed conversion ratio. While it has been reported that organic acid did not influence feed intake in laying hens ( Dahiya et al., 2016 ), it has been shown that organic acid can increase egg weigh ( Grashorn et al., 2013 ). The results of this study highlight the inconsistency of the responses to acidifiers which could be because of several factors including the buffering nature of some dietary ingredients and the heterogeneity of the gastrointestinal microbiota ( Pearlin et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Bahnas (2009) reported an increase in the laying rate of Japanese quail supplemented with 0.05% malic acid. Dahiya et al (2016) concluded that laying hens supplemented with salts of organic acids had higher hen-d egg production. Hidalgo (2009) reported an increase of up to 16% in egg production when birds ingested LV with the feed.…”
Section: Discussionmentioning
confidence: 99%
“…Bu çalışmada, hayvan materyali olarak 96 adet tüm aşıları yapılmış olan 28 haftalık yaştaki Lohmann (LSL) tipi beyaz yumurtacı tavuk, her biri 6 alt gruptan oluşan biri kontrol olmak üzere toplam dört gruba ayrılarak, tavuklar, her bir kafeste 4 tane olacak şekilde tam şansa bağlı deneme desenine göre üç katlı batarya tipi kafeslere (46 * 46 * 50 cm) yerleştirilmişlerdir. (Dahiya et al 2016) yemden yararlanma oranının iyileştiği rapor edilirken, yumurtacı tavuk rasyonlarına değişik seviyelerde propiyonik asit (Oruwari, 1993) ve farklı organik asit karışımlarının ilavelerinin (Kaya et al, 2013;Kaya et al, 2014;Gül et al, 2014) (Park et al, 2009). Organik asitler içerisinde en yüksek pKa değerine propiyonik asit sahip olduğundan dolayı gastrik pH üzerine daha etkili olduğu ve böylece yumurta kabuğunun en önemli minerali olan Ca absorbsiyonu iyileştirerek yumurta kabuk kalınlığını iyileştirdiği düşünülmektedir.…”
Section: Materyal Ve Yöntemunclassified
“…Günümüzde, yaklaşık olarak 60 adet organik asit (fumarik asit, malik asit, sitrik asit formik asit vb gibi) tanımlanmış (Park et al 2009) Bu çalışmadan farklı olarak yumurtacı tavuk rasyonlarına farklı seviyelerde organik asit karışımı (propiyonik asit, formik asit ve onların tuzları) ilavesiyle yürütülen bir araştırmada (Yeşilbağ and Çolpan, 2006) yumurta veriminin kontrole göre artırdığı, yemden yararlanma oranının doza bağlı olmamakla birlikte kontrole göre düştüğü ifade edilmiştir. Yine benzer başka bir çalışmada yumurtacı tavuk rasyonlarına kalsiyum propiyonat ilavesinin (Dahiya et al 2016) yemden yararlanma oranının iyileştiği rapor edilirken, yumurtacı tavuk rasyonlarına değişik seviyelerde propiyonik asit (Oruwari, 1993) ve farklı organik asit karışımlarının ilavelerinin (Kaya et al, 2013;Kaya et al, 2014;Gül et al, 2014) (Park et al, 2009). Organik asitler içerisinde en yüksek pKa değerine propiyonik asit sahip olduğundan dolayı gastrik pH üzerine daha etkili olduğu ve böylece yumurta kabuğunun en önemli minerali olan Ca absorbsiyonu iyileştirerek yumurta kabuk kalınlığını iyileştirdiği düşünülmektedir.…”
Section: Introductionunclassified